A case study on the development of desegregation in USD 501 in Topeka, Kan., the home of the desegregation movement - Fisher, Tory C. (Kansas State University, 2011)
This case-study focuses on the desegregation processes that occurred in USD 501 in Topeka, Kan. USD 501 is the Topeka public school district addressed by the Supreme Court in the infamous Brown v. Board of Education, which is the case credited with ending the legal racial segregation of children in public schools. The Supreme Court ordered the subsequent disbandment of all racial segregation in public school districts in1955. However, USD 501 did not successfully carry out this order for nearly forty years. Therefore, the primary question of this thesis is, "Why was there a forty year delay in the creation of desegregation plan in USD 501?" This research question is, however, a multipart question and therefore required answering the following associated questions: 1) what is the definition of desegregation?; 2) What does desegregation look like?; and 3) did desegregation occur in USD 501? Through the use of sociological theories and court records, I was able to answer each of the associated questions, as well as discern the answer the main thesis question. The reason for the forty year delay in the development and implementation had a two part answer: 1) socially reproductive action was often used to reinforce social and spatial inequalities in Topeka itself, which maintained the racial segregation of USD 501 schools; and 2) the expectations of the desegregation process changed over time. This led to the second of the main thesis questions which was, " How was desegregation originally defined in the Brown case, how is it understood currently, and how did its definition change over time?" I found that the new expectations of desegregation were tied to a 1968 Supreme Court case, which established the Green Codes for the desegregation process. The Green Codes structured the court's assessment of desegregating districts, which made identifying informal actions that promote segregation more identifiable. Then I examined the effect of the desegregation plan's inception in USD 501. A correlation was found between the desegregation plan's inception and declining white enrollment, which lasts approximately thirteen years. I then summarize the research findings, and use sociological theory to support the conclusions.
Keywords: Desegregation; Race; Social Reproduction; Education; Sociology; Sociology (0626)